THE ROLE OF YASAWI'S IDEOLOGY IN ENSURING STABILITY IN SOCIETY - Khamzaev Shavkat Abdirasulovich (Scholar Express Journal, 2023)
This scientific article presents a socio-philosophical analysis of the Yasawi Order as an ideological reflection of socio-economic changes in society. The authors explore the role of this order in providing answers to life's problems and finding ways to achieve excellence.
Keywords: Islam; Sufism; tariqa; stability